2013
DOI: 10.5539/jedp.v3n2p89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Testing to the Development of Vocabulary, Nominal Structures and Verbal Morphology

Abstract: The repeating testing has shown to increase the general proficiency level of the students. Metsämuuronen (2013) showed with an experimental study that the overall achievement level in a secondary language enhanced statistically significantly whit repeated testing design. Previously, Tuvling (1967) and showed with a laboratory experiment that remembering the material studied is the most efficient with repeated testing sessions rather than with repeated studying sessions. An explanation for this, given by Lasr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…Their experiments showed that delayed recall is optimized, not with repeated studying sessions, but with repeated testing sessions. Metsämuuronen (2013); also, Metsämuuronen and Mattsson (2013) shows practical results supporting this theoretical result. The result was re-interpreted by Lasry et al (2008).…”
Section: Memory and Cognitive Modelssupporting
confidence: 76%
See 1 more Smart Citation
“…Their experiments showed that delayed recall is optimized, not with repeated studying sessions, but with repeated testing sessions. Metsämuuronen (2013); also, Metsämuuronen and Mattsson (2013) shows practical results supporting this theoretical result. The result was re-interpreted by Lasry et al (2008).…”
Section: Memory and Cognitive Modelssupporting
confidence: 76%
“…The relevance of these triggers from the contemporary thinking of memory viewpoint is that repeating the material is an effective device for remembering (e.g., Tulving, 1967; Baddeley, 1997) though not as effective as the repeated testing of the material studied (Tulving, 1967; Karpicke and Roediger, 2008; Metsämuuronen, 2013; Metsämuuronen and Mattsson, 2013). This may lead to multiple traces to the memory (Lasry et al, 2008); in the modern teaching processes these multiple traces can be enhanced by using feedback via cues during the task process and specifically with the aid of learning technologies (Hattie and Timperley, 2007; Van der Kleij et al, 2015).…”
Section: Bruner and Mnemonic Triggersmentioning
confidence: 99%
“…The effects of retrieval practice in L2 learning have also been examined by few studies (Barcroft, 2007; Kang et al, 2013; Metsamuuronen and Mattsson, 2013), although these have revealed retrieval practice advantages for both word learning and general language measures. In one study, performed in the laboratory, native English speakers learning Spanish were trained on picture–word pairs (with novel Spanish words) under either retrieval practice or restudy conditions (Barcroft, 2007).…”
Section: Spaced Repetition and Retrieval Practice In Language Learnmentioning
confidence: 99%
“…Another laboratory study found retrieval practice advantages (as compared to repeating after a native speaker) for both comprehension and production of Hebrew words in English native speakers (Kang et al, 2013). In another study, carried out in the classroom, adult learners of Hebrew either studied or were tested on Hebrew material ranging from grapheme-recognition to vocabulary and grammar production, twice a week for several weeks (Metsamuuronen and Mattsson, 2013). At the end of training, students in the retrieval practice condition had improved significantly more than students in the study condition, compared to a pre-test.…”
Section: Spaced Repetition and Retrieval Practice In Language Learnmentioning
confidence: 99%
“…The dimensions can easily be connected to the modern theories of long-term memory discussed within the cognitive psychology (see the condensed discussion about the concepts from the learning point of view in Metsämuuronen & Mattsson, 2013). The basic theories of human mind claim that human long-term memory includes two parts: declarative and procedural (or non-declarative) memory (e.g.…”
Section: Dimensions In the Common Standardsmentioning
confidence: 99%